PESANTREN: LEMBAGA PENDIDIKAN SEKALIGUS KQMUNITAS ISLAM YANG KHAS, SEBUAH AKULTURASI BUDAYA: Pesantren (Islamic boarding school), traditional, Islamic, cultural acculturation. - Zaman, Achmad Qomaru (Buana Pendidikan, 2011)
Pesantren (Islamic Boarding School) is a traditional institution for Muslims, founded among 13th-15th century, which teaches the importance of religious morality to guide everyday behavior. In its development, the schools not only teach religious sciences, but also general science. Instead of educational and social institution, Pesantren is as well as religious broadcasters institutions. The students' community actually is an Islamic society which consists of groups of students bound together by tradition and systems, custom and law "ecology" unique and rarely found its similarity to other communities outside of schools. The traditional Pesantren is a form of cultural acculturation outcomes of Indonesian with Islam. The tradition of local school is a religious phenomenon that has the function of connecting between Islamic values with the culture of Indonesia, and eventually formed the National Islamic nation state. As the concept of nationalism, this paradigm can be used for the purposes of normative constitutional foster as a sense of nationalism. With the acculturation culture model, Indonesia will be free from formalism primordial of Islam and local customs.